Designed amphiphilic polystyrene as surfactant for oligo(p-phenylenevinylene)-incorporated PS nanobeads and visual detection of bilirubin in human blood serum - Makkad, Sarabjot Kaur; Asha, S. K. (ACS Applied Polymer Materials, 2019)
Amphiphilic polystyrene having pendant glucuronic acid (PS-DGlu) was designed and systematically synthesized to be used as a stabilizing agent in styrene miniemulsion polymerization, while covalently incorporating oligo(p-phenylenevinylene) (OPV)-based fluorophore to prepare PSG-OPV-n. This OPV fluorophore was incorporated with an aim to work as a signal transducer, while glucuronic acid on the surface of PS nanobeads would act as the water solubilizing moiety for PS to enable it to function as surfactant and also serve as an interaction site for free bilirubin to facilitate noncovalent interaction via hydrogen bonding. Efficient energy transfer from OPV to bilirubin was observed, owing to the appreciable spectral overlap between emission of OPV and absorption of bilirubin. Visual color change from blue to bluish green was observed under an UV lamp after the addition of bilirubin into the polymer. Selectivity of the sensor was checked among the pool of other interferences, such as glucose, sucrose, metal ions, cholesterol, and biliverdin. The limit of detection was found to be as low as 20 nM, which is far less than the clinical range for causing jaundice (<25 to >50 mu mol/L). Moreover, the developed sensor showed its effectiveness toward real time monitoring of free bilirubin in human serum.
Keywords: amphiphilic homopolymer; bilirubin; functionalized polystyrene nanobeads; oligo(p-phenylenevinylene); sensing